1971
DOI: 10.1093/bja/43.1.14
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Clinical Study of Ct1341—a Steroid Anaesthetic Agent

Abstract: The effects of a new steroid anaesthetic agent (CT1341) were studied in twenty volunteers divided into three groups. In group I, serial measurements were made of heart rate, blood pressure and respiratory rate. In group II, detailed haemodynamic studies were made in patients undergoing diagnostic cardiovascular investigations. These studies included measurement of cardiac output, stroke volume and arterial blood gases. In group HI, time from induction to "true recovery" was measured following a single intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
2

Year Published

1972
1972
1995
1995

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 0 publications
0
28
2
Order By: Relevance
“…It is a potent intravenous anaesthetic in animals, which produces rapid induction of anaesthesia without vascular irritation. The initial trials of CT 1341 in man (Campbell, Forrester, Miller, Hutton, Kennedy, Lawrie, Lorimer & McCall, 1971;Savege, Foley, Coultas, Walton, Strunin, Simpson & Scott, 1971;Clarke, Montgomery, Dundee & Bovill, 1971;Swerdlow, Chakraborty & Zahangir, 1971) appear to substantiate the findings in animals.…”
Section: Introductionmentioning
confidence: 67%
“…It is a potent intravenous anaesthetic in animals, which produces rapid induction of anaesthesia without vascular irritation. The initial trials of CT 1341 in man (Campbell, Forrester, Miller, Hutton, Kennedy, Lawrie, Lorimer & McCall, 1971;Savege, Foley, Coultas, Walton, Strunin, Simpson & Scott, 1971;Clarke, Montgomery, Dundee & Bovill, 1971;Swerdlow, Chakraborty & Zahangir, 1971) appear to substantiate the findings in animals.…”
Section: Introductionmentioning
confidence: 67%
“…The injection is formulated as follows: Preliminary studies have indicated that CT 1341 is a promising intravenous anesthetic agent characterized by immediate induction of anesthesia of short duration, and rapid and uncomplicated recovery from anesthesia (Child et al 1971;Campbell et al 1971;Clarke et al 1971;Savege et al 1971;Swerdlow et al 1971). In regard to cardiovascular effects, Campbell et al (1971) reported a slight fall in blood pressure and stroke volume and a significant rise in heart rate with minimal changes in cardiac output. Savege et al (1971) also reported a well-sustained cardiac output associated with a considerable fall in systolic blood pressure and increase in heart rate.…”
mentioning
confidence: 99%
“…Minaxolone was also water soluble. Early clinical studies showed that recovery was relatively slow [3,4], but it was withdrawn prior to release as the result of toxicological studies in animals.Althesin (alphaxolone/alphadolone) approached the ideal intravenous anaesthetic, with acceptable cardiorespiratory effects and rapid recovery [5]. Its pharmacokinetic properties allowed its use by continuous infusion and it was the first intravenous anaesthetic that could be used as the hypnotic component of total intravenous anaesthesia [6] and for sedation in the intensive care unit [7] and yet allow acceptable rates of recovery.…”
mentioning
confidence: 99%